Boundary layer flow of mixed convection viscoelastic micropolar fluid over a horizontal circular cylinder with aligned magnetohydrodynamic effect - Laila Amera, Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Wan Nur Syahidah, Wan Yusoff (UTM Press, 2017)
The boundary layer flow of a viscoelastic micropolar fluid over a horizontal circular cylinder with aligned magnetohydrodynamic effect is considered. The governing boundary layer equations are transformed into non dimensional form by using appropriate dimensionless variables. The non-dimensional governing equations are then transformed into similarity equations and solved using an implicit finite difference scheme known as the Keller box method. Numerical results on the distributions of velocity and temperature of fluid are obtained for a range of values of magnetic parameter, M, viscoelastic parameter, K, material parameter, L, and mixed convection parameter, . The graphical representation of the results are presented and it shows the investigated parameters are significance and affected the fluid flow.